Les jardins partagés en Finlande - Hanna Sorsa (In Situ, 2018)
With urbanization and the increasing density of housing in cities, community gardens were first used as food resources for the poor, then for the middle classes, before becoming places of relaxation and recreation towards the end of the twentieth century. Nowadays, in Finland, their use, construction and preservation are controlled by several regulations. The most important community gardens – nine in Helsinki – are classified in the “yleiskaava” as outstanding places in terms of landscape, architectural and cultural heritage. Large cities face the challenge of extending these gardens in reply to growing demand from inhabitants, whilst preserving the original spirit of the places concerned. The purpose of this paper is to present the latest research on this topic in Finland. Among many articles published recently, particular attention is paid to that of Maria Karisto on the work of Elisabeth Koch (2015), Gretel Hemgård on the Kumpula education garden (2016) and Siivonen, Salonen and Kuchka on allotment gardens (1999). These articles illustrate the characteristics and the problems concerning the conservation of community gardens from the historical point of view. They also present the landscape gardeners, humanists and gardeners who were at the origins of the community gardens. Finally, the article reports on specific issues relating to the maintenance of this living heritage.